(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The current research aim is to analyse the impact of workplace incivility on organizational dissent with Interactional Justice among safety personnel. However, for the purpose of this primary quantitative research method was used, and information was derived from 360 health professionals having 4 years of job experience. For data analysis demographic, descriptive and correlation analysis were used through using SPSS software. Further, Confirmatory factor analysis and SEM model has been used via using Smart PLS. Hence, findings revealed that workplace incivility has a positive and significant influence on the interactional justice. Additionally, workplace incivility has also a significant and negative influence on organisation dissent. Whereas interactional justice has insignificant influence on organisation dissent. Thus, it is essential for organisations to place a high priority on developing a culture of kindness, compassion, and fairness in order to foster workplace incivility interactional justice and organisation dissent.